EXPLORING GREEN FINANCING AND ITS CHALLENGES IN MALAYSIAN REAL ESTATE PROJECT - Yusni Kamal, Nurulshalina; Mohd Adnan, Yasmin; MOHD FOUDZY, DR. NOORAME; Razali, Muhammad Najib (Journal of Surveying, Construction and Property, 2024)
This paper aims to explore the landscape of green financing adoption in Malaysia's real estate sector and its challenges for sustainable real estate development. It attempts to uncover the challenges of incorporating green finance into real estate projects and comparing the challenges faced by the local players with the global players. The results will allow recommendations to be made for successful green financing in Malaysia. The examination of Malaysia's present green finance adoption is made through a qualitative approach. Interviews were conducted with real estate developers and local financial organisations for the achievements of the main objectives. The findings found that the challenges faced by stakeholders in the implementation of green finance in real estate in Malaysia such as the lack of consistency in defining green terms, public awareness of green financing and projects, profitability uncertainty, limited green finance initiatives, longer green finance processes, and a lack of green efficiency data. In order to address these challenges, several recommendations were suggested which include standardising terminology, raising public awareness, providing financial incentives, improving funding accessibility, streamlining procedures, and strengthening data collection and transparency. Thus, the findings provide the potential to pave the path for widespread adoption of green financing in Malaysia's real estate sector by overcoming constraints such as restricted rules and incentives.